SILICON RELEASE FROM HYDROXYAPATITES IN WATER AND SIMULATED BODY FLUID - CADAR, Oana; FRANGOPOL, †Petre T.; TOMOAIA, Gheorghe; OLTEAN-DAN, Daniel; PALTINEAN, Gertrud Alexandra; MOCANU, Aurora; HOROVITZ, Ossi; TOMOAIA-COTISEL, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Nanostructured hydroxyapatite (HAP) and silicon substituted hydroxyapatites (HAP-Si), with 0.47 and 2.34 wt% Si, were prepared by wet precipitation method. Their structure was investigated by X rays diffraction (XRD), FTIR spectroscopy, energy dispersive X ray (EDX) spectroscopy and their images were obtained by TEM, SEM and AFM. Their behavior in water and SBF was investigated by inductively coupled plasma optical emission spectrometry (ICP-OES) for an immersion time from 1 to 90 days. While Ca and P release from HAP is very low, the presence of Si enhances greatly their release in water, along with a continuous and long lasting Si release. In simulated body fluid, SBF, Ca, P and Mg are removed from the solution, by the formation of a new HAP enriched in Mg, while silicon is released as in water. Thus, Si doped HAP might have advantageous applications as bone and tooth materials.